A remote sensing-based method for drought monitoring using the similarity between drought eigenvectors. Issue 23 (2nd December 2019) - Song, Chao; Yue, Cuiying; Zhang, Wen; Zhang, Dongying; Hong, Zhiming; Meng, Lingkui
ABSTRACT: The land surface temperature (LST) and vegetation growth status are two direct indicators of drought. In this study, we selected the LST index and vegetation index to construct drought eigenvectors, then proposed a new remote sensing drought index to assess the drought severity by calculating the similarity between the drought eigenvector of the target pixel and the drought eigenvector under an extremely wet state. Considering the different responses of various objects to drought, the drought eigenvectors of different land cover types were established. The results showed that the Temperature-Vegetation Water Stress Index (T-VWSI) were highly correlated with the measured relative soil moisture (RSM). The correlation coefficients ( r ) between the T-VWSI and 20-cm RSM reached 0.81, 0.77, and 0.78 in May, June, and July, respectively. Therefore, the T-VWSI is a promising drought index that will play an important role in drought monitoring.